2020
DOI: 10.3390/nano10010137
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Tribological and Anticorrosion Performance of Waterborne Polyurethane Coating by the Synergistic Effect between Modified Graphene Oxide and Polytetrafluoroethylene

Abstract: In this work, the effect of modified graphene oxide and polytetrafluoroethylene (PTFE) on the tribological and anticorrosion properties of waterborne polyurethane (WPU) was studied. The modified graphene oxide (MGO) was obtained by the surface functionalization modification of graphene oxide (GO) with isophorone diisocyanate (IPDI), and MGO/WPU composite coating and MGO-PTFE/WPU composite coating with different mass fractions of MGO were prepared. The tribological and electrochemical experiment results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Zhang et al [ 17 ] have also shown that the addition of triethylene tetramine + polyethylene glycol diglycidyl ether functionalized GO enhanced the water resistance, the thermal stability, and the mechanical properties of PUDs. Furthermore, different GO derivatives have been used to improve the anticorrosive properties of coatings made from PUDs [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 17 ] have also shown that the addition of triethylene tetramine + polyethylene glycol diglycidyl ether functionalized GO enhanced the water resistance, the thermal stability, and the mechanical properties of PUDs. Furthermore, different GO derivatives have been used to improve the anticorrosive properties of coatings made from PUDs [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 Among various polymers, WPU has a wide range of applications in the friction field because of its excellent mechanical properties, easy modification, environmental protection, and no pollution. 7 9 However, pure WPU cannot meet the requirements of antifriction and wear resistance under high-strength conditions. The tribological properties of the polymer can be improved by adding lubricants such as molybdenum disulfide, 10 , 11 graphite, 12 and polytetrafluoroethylene.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] So GO is widely used as a filler in polymer-based composites to improve the dielectric properties, [5,6] mechanical properties, [7][8][9] and anticorrosive properties. [10,11] However, due to the strong van der Waals force between the GO nanosheets; moreover, graphene-based nanocomposites are usually fabricated by the method of solution casting, it is difficult to uniformly disperse GO in polymers, especially in non-polar polymers. Generally, a good dispersion of GO within the polymer matrix is necessary to improve the properties of composites.…”
Section: Introductionmentioning
confidence: 99%